Simultaneous rupture propagation through fault bifurcation of the 2021 Mw7.4 Maduo earthquake - Wei, Shengji (2023)
Fault geometric complexity plays a critical role in earthquake rupture dimension. Fault bifurcations are commonly observed in earthquake geology, yet, robust kinematic rupture processes on bifurcated fault branches are largely missing, limiting our understanding of rupture dynamics and seismic hazard. Here, we holistically study the fault geometry and bilateral rupture of the 2021 Mw7.4 Maduo, China earthquake, that shows clear fault bifurcation near its eastern terminal. We integrate space geodesy imaging, back-projection of high-frequency teleseismic array waveforms, multiple point source and finite fault inversions, and constrain in detail the rupture process, in particular, through its fault bifurcation. Our models reveal a stable rupture speed of ∼2.5 km/s throughout the entire rupture and a simultaneous rupture through fault branches bifurcated at 20°. The rupture on bifurcated faults radiated more high-frequency waves, especially from the stopping phases. The stopping phase on the southern branch likely stopped the rupture on the northern branch.